Subgenera Cladoconnus Reitter and Tetramelus Motschulsky of Euconnus Thomson discovered in China (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
The occurrence of Euconnus subgenera Cladoconnus and Tetramelus in China is recorded for the first time, with ten new species. Euconnus pingpong sp. nov. and E. sagittarius sp. nov. are placed in Cladoconnus, and eight species are placed in Tetramelus: E. punctator sp. nov., E. aurilobatus sp. nov., E. magnirufus sp. nov., E. tetraspinosus sp. nov., E. gansuminor sp. nov., E. microrufus sp. nov., E. sinespinosus sp. nov., and E. mediorufus sp. nov. The presence of Cladoconnus in China was expected, as this subgenus occurs in the Russian Far East, on the Korean Peninsula and in Japan. Euconnus sagittarius belongs to the E. ussuriensis species group of Cladoconnus, while E. pingpong seems to be remotely related to this species complex. All Chinese species of Tetramelus are wingless, microphthalmous, and males have strongly impressed metaventrites. They show close similarities to the European E. oblongus species group, into which they can be included. The unique character of seven out of eight newly described species of Tetramelus is a male metatrochanteral (and in one case additionally protrochanteral) modification.